Mobile Pantries Can Serve the Most Food Insecure Populations (Health Equity, 2022)
Purpose: Food insecurity is an urgent crisis in the United States, with one in nine people lacking a consistent source of the food necessary for an active and healthy lifestyle. This crisis is particularly dire in Maricopa County, Arizona, where 1 in 5 children experience food insecurity, and >1 in 10 residents experience poverty. Mobile food pantries offer an additional resource to address food insecurity; however, there is minimal knowledge about how communities utilize these food distributors. Background: Research on the elderly (people >60 years) and immigrant populations shows that these populations are especially vulnerable to food insecurity. The risk these groups face is compounded in Maricopa County, the 15th largest county in the country with minimal public transit to extant resources. Mobile food pantries offer one solution to this issue, bringing groceries and other important items directly to communities. Methods: This study utilizes data from a food pantry called ?Phoenix Rescue Mission? (PRM) on food insecure people's use of PRM's mobile and brick-and-mortar pantries, as well as census data. Using GIS mapping and a multinomial logistic regression model, this research identifies how different demographic groups engage with PRM's brick-and-mortar or mobile pantries. Results: Findings indicate that people aged 60?80 years and immigrant people of color are more likely to use both mobile and brick-and-mortar pantries. Conclusions: This research suggests that mobile pantries can reach the most food insecure populations and local nonprofits and governments can consider implementing mobile pantries to reach food insecure communities.